The Personal Computer and Entrepreneurship - Fairlie, Robert W. (Management Science, 2006)
In contrast to the large and rapidly growing literature on information technology (IT) investments and firm productivity, we know very little about the role of personal computers in business creation. Using matched data from the 1997–2001 Computer and Internet Usage Supplements to subsequent Outgoing Rotation Group files from the Current Population Survey (CPS), I explore the relationship between computer ownership and entrepreneurship. Trends over the past two decades provide some evidence of a positive relationship between home computers and entrepreneurship rates, but the evidence is not clear. In contrast, an analysis of the relationship between computer ownership and entrepreneurship at the individual level provides evidence that individuals who had access to a home computer are substantially more likely to become entrepreneurs over the following 12–15 months. Probit and bivariate probit regressions also provide evidence of a strong positive relationship between computer ownership and entrepreneurship among women, but only limited evidence for men. Further, estimates from the CPS indicate that entrepreneurs who had prior access to home computers create a large variety of types of businesses and not only those in the IT industry.